2016 IEEE International Symposium on Information Theory (ISIT) 2016
DOI: 10.1109/isit.2016.7541712
|View full text |Cite
|
Sign up to set email alerts
|

Fairness in communication for omniscience

Abstract: Abstract-We consider the problem of how to fairly distribute the minimum sum-rate among the users in communication for omniscience (CO). We formulate a problem of minimizing a weighted quadratic function over a submodular base polyhedron which contains all achievable rate vectors, or transmission strategies, for CO that have the same sum-rate. By solving it, we can determine the rate vector that optimizes the Jain's fairness measure, a more commonly used fairness index than the Shapley value in communications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…It is shown in [54] that the problem min{ i∈V r 2 i wi : r V ∈ R * ACO (V )} can be solved in O(|V | 2 · SFM(|V |)) time, where |V | = 5 for the system in Example III.11. But, if we compute the minimizer of (20) for each subset C in the fundamental partition P * , the problem can be solved in O(η 2 · SFM(η)) time, where η = max{|C| : C ∈ P * } = 3.…”
Section: A Properties Of Minimal/finest Separatorsmentioning
confidence: 99%
“…It is shown in [54] that the problem min{ i∈V r 2 i wi : r V ∈ R * ACO (V )} can be solved in O(|V | 2 · SFM(|V |)) time, where |V | = 5 for the system in Example III.11. But, if we compute the minimizer of (20) for each subset C in the fundamental partition P * , the problem can be solved in O(η 2 · SFM(η)) time, where η = max{|C| : C ∈ P * } = 3.…”
Section: A Properties Of Minimal/finest Separatorsmentioning
confidence: 99%
“…9 This means that Algorithm 3 cannot be applied to the non-asymptotic model by simply running each stage k of Algorithm 3 at the integer-valued 8 This is the case since, in the first stage k = 1, the rate vector r . Independent from this successive approach, there are several algorithms proposed in [25] for searching the fairest optimal rate vector for both asymptotic and non-asymptotic models. 9 An example is the rate r α,3 in (6), where r 7,3 = 1 but r 9,3 = 0 so that the monotonicity in Proposition V.1(b) does not hold.…”
Section: Non-asymptotic Modelmentioning
confidence: 99%
“…The optimization goal is to minimize the total number of transmissions [1], [2], [3], [4]. It has been shown that, for the fully connected network cases, the CDE problem can be formulated as an Integer Linear Program with the Slepian-Wolf constraints on all proper subsets of the packet distribution information of nodes.…”
Section: A Related Workmentioning
confidence: 99%
“…A randomized algorithm was proposed to estimate the minimum number of required transmissions [5]. Deterministic algorithms based on Dilworth Truncation optimization were proposed to compute the exact minimum number of required transmissions [3], [4], [6]. It has been recently shown that a deterministic algorithm based on conditional basis construction [1] can solve this optimization problem with lower complexity.…”
Section: A Related Workmentioning
confidence: 99%
See 1 more Smart Citation